2021
DOI: 10.3389/fnhum.2021.719502
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of the Whole Foot Soles Surface Using an Inexpensive Portable Device to Investigate Age-Related Alterations of Postural Control

Abstract: Background: Standing on a foam surface is used to investigate how aging affect the ability to keep balance when somatosensory inputs from feet soles become unreliable. However, since standing on foam also affects the efficacy of postural adjustments, the respective contributions of sensory and motor components are impossible to separate. This study tested the hypothesis that these components can be untangled by comparing changes of center of pressure (CoP) parameters induced by standing on a foam pad vs. a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Prior investigators have shown that stationary tactile stimuli to the sole changes the body sway in quiet stance (Lauzier et al, 2021; Sawaguchi et al, 2022; Wang & Yang, 2012). In our study, COP length, representing the total amount of the body sway in time, was not changed by moving tactile stimuli to the sole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior investigators have shown that stationary tactile stimuli to the sole changes the body sway in quiet stance (Lauzier et al, 2021; Sawaguchi et al, 2022; Wang & Yang, 2012). In our study, COP length, representing the total amount of the body sway in time, was not changed by moving tactile stimuli to the sole.…”
Section: Discussionmentioning
confidence: 99%
“…In elderly adults with a history of frequent falls, tactile stimulation to the sole improved body sway in quiet stance (Wang & Yang, 2012). Tactile stimuli to the sole increased the COP displacement and velocity in quiet stance (Lauzier et al, 2021). Taken together, these investigators illustrated that stationary tactile stimuli to the sole influenced body sway in quiet stance.…”
Section: Introductionmentioning
confidence: 99%